Pilgrims were they all?: aspects of pilgrimage and their influence on Old and Middle English literature - Dyas, Dee (1998)
Pilgrims are so frequently encountered in the pages of medieval literature that their presence (and significance) can easily be overlooked. Moreover, the visiting of holy places formed such an integral part of medieval religion that critics often assume it to have constituted the primary meaning of pilgrimage in medieval thought. Pilgrimage is consequently treated as a given fact of medieval life, a pious exercise which some writers, more creative than the rest, chose to craft into an image of life and inward growth. The reality is more complex and fascinating by far. Pilgrimage, as understood by the medieval church, was not a monolithic concept but a mosaic of ideas which had evolved through the centuries, the product of both syncretism and heated debate.